Vulnerability to Drought and Food Price Shocks : Evidence from Ethiopia - Hill, Ruth Vargas; Porter, Catherine (Elsevier, 2018)
While the measurement and determinants of poverty have been widely studied, vulnerability, or the threat of future poverty, has been more difficult to investigate due to data paucity. We combine nationally representative household data with objective drought and price information to quantify and investigate causes of vulnerability to poverty in Ethiopia. Previous estimates have relied on self-reported shocks and variation in outcomes within a survey, which is inadequate for shocks such as weather and prices that vary more across time than space. We used historical distributions of climate and price shocks in each district to simulate the probable distribution of future consumption for individual households and use these quantify vulnerability to poverty. We find that many Ethiopians are unable to protect their consumption against lack of rainfall and sudden increases in food prices. A moderate drought causes a 9% reduction in consumption for many rural households and recent high inflation has caused a 14% reduction in the consumption of uneducated households in urban areas. We also find that the vulnerability of rural households is considerably higher than that of urban households, despite realized poverty rates being fairly similar. This reflects the fact that the household survey in 2011 was conducted during a year of good rainfall but rapid food price inflation. The results highlight the need for caution in using a snapshot of poverty to target programs, as underlying rates of vulnerability can be quite different from the poverty rate captured at one point in time. The results also suggest that significant welfare gains can be made from risk management in both rural and urban areas.